Motivating a fine-grained syntax of Arabic prepositional phrases - Fassi Fehri, Abdelkader; Alrawi, Maather (Frontiers in Language Sciences, 2024)
The paper provides a novel motivation in favor of a complex and fine-grained syntax of spatial PPs in Arabic. It neatly fills a gap between the complex semantics of spatial expressions and their morphosyntax, which remains unexplained using wide spread cognitive approaches. We propose a fine-grained architecture of root nodes, categories, and features in the basic representations of Path/Place expressions, inspired by cartographic analyses of PPs, but based on a pP dual-projection model, separating the root/lexical part from the functional/categorial part, as in Distributed Morphology (= DM). In so doing, the paper challenges traditional analyses of PPs as projecting a uniform Path over Place structure (with no bifurcating domain separation). It also provides essential ingredients allowing the decomposition of Place and Path words or expressions, including COINCIDENCE, CONTAIN, CONTACT, etc., or syntactic projections such AxPs, DeixPs, DegPs, ScaleP, GoalPs, etc, which play important syntactico-semantic roles in the grammar. Our analysis successfully accounts for complexity of prepositions or spatial expressions, their morphosyntactic alternations, variation, and polysemy.